Double-ion Yb < 3 + >-Li < + > doped rare earth Pr < 3 + >: Y2SiO5 up-conversion material hydrogel dressing as well as preparation method and application thereof

By using hydrogel dressings with double ion Yb3+-Li+ doped with rare earth Pr3+:Y2SiO5 upconverting material in skin wound treatment, the problems of insufficient antibacterial properties and lack of viscosity in existing treatment methods are solved, and efficient and safe wound healing and antibacterial effects are achieved.

CN119701074APending Publication Date: 2025-03-28CHANGZHOU UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411749197.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-11-12
Filing Date
2024-12-02
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing skin wound treatment methods lack antibacterial properties, and the dressings need to be frequently replaced, and the cotton gauze lacks stickiness, which leads to inconvenience in treatment, and some patients have an allergic reaction to medical tape.

Method used

A (CBC-PDA) hydrogel dressing of two-ion Yb3+-Li+ doped rare earth Pr3+:Y2SiO5 upconverting material (CBC-PDA) was designed. The lattice field around the rare earth ions was optimized by introducing metal Li+ ions and Yb3+ ions, thereby improving the upconversion luminescence intensity, and mixing the material with a hydrogel substrate to prepare a dressing with excellent mechanical properties, viscosity and antibacterial properties.

Benefits of technology

It improves the targeting of phototherapy, reduces the number of treatments, enhances the deep antibacterial and healing effects, and provides an efficient, safe and convenient wound treatment method, suitable for clinical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005164561530000091
    Figure BDA0005164561530000091
  • Figure HDA0005164561540000011
    Figure HDA0005164561540000011
  • Figure HDA0005164561540000021
    Figure HDA0005164561540000021
Patent Text Reader

Abstract

The invention relates to a hydrogel dressing of bacterial cellulose doped with a double-ion Yb < 3 + >-Li < + >-coated Pr < 3 + >: Y2SiO5 up-conversion material as well as a preparation method and application of the hydrogel dressing. The preparation method comprises the following steps: preparing CBC-PDA hydrogel from dopamine carboxylated BC and dopamine conjugated aldehyde modified hyaluronic acid, adding a double-ion-doped Yb < 3 + >-Li < + >-coated Pr < 3 + >: Y2SiO5 up-conversion material, and mixing to prepare the hydrogel (CBC-PDA) dressing of the up-conversion material. According to the invention, by adjusting the doping concentration of Li < + > ions, the symmetry and local environment of a crystal field are changed, so that the upconversion luminescence capability of rare earth ions is enhanced. Under 980nm excitation laser, the ytterbium ion and lithium ion doped Pr < 3 + >: Y2SiO5 up-conversion material effectively converts far infrared light into ultraviolet light, the fluorescence intensity is greatly improved, and the up-conversion efficiency is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biomedical materials and optical materials, and specifically relates to a double ion Yb 3+ -Li + Doped rare earth Pr 3+ :Preparation method and application of Y2SiO5 upconversion material and its hydrogel dressing. Background Art

[0002] The widespread existence of skin injuries makes wound healing one of the important issues in the biomedical field. In real life, abrasions, cuts, and skin incisions after surgery are more common. In clinical practice, most skin wounds are disinfected with 75% alcohol or iodine, and then covered with cotton gauze or 3M dressings. Since cotton gauze or dressings lack antibacterial properties, they need to be disinfected and replaced regularly. In addition, on the one hand, gauze dressings may shed impurities such as fibers that affect wound healing; on the other hand, cotton gauze lacks stickiness and needs to be fixed with medical tape to apply to the wound, and some patients will have allergic reactions to medical tape. Therefore, it is of great clinical significance to explore an efficient, safe, and convenient wound treatment method.

[0003] Stokes' law states that a material can only emit low-energy light when it is excited by high-energy light, that is, when it is excited by short-wavelength, high-frequency light, the material emits long-wavelength, low-frequency light. Upconversion luminescence is the opposite, which means that when a material is excited by low-energy light, it emits high-energy light, that is, when it is excited by long-wavelength, low-frequency light, the material emits short-wavelength, high-frequency light. Pure Pr 3+ :Y2SiO5 upconversion material can emit 290nm ultraviolet light under 415nm wavelength excitation light. However, ultraviolet light therapy has the following disadvantages: skin resistance to local treatment, systemic immunosuppression, systemic infection, and high recurrence rate (90%). There is an urgent need to develop safer and more effective drugs to allow long-term and continuous disease control. However, far-infrared light can penetrate deeper tissues and is suitable for treating deep pain and promoting blood circulation; through vasodilation, it can effectively improve local blood circulation and help eliminate toxins in the body; far-infrared light has no ionizing radiation, high safety, and is not easy to damage tissues, which is suitable for long-term treatment; it is widely used in pain management, wound healing, and immunity enhancement, and has good prospects, and the equipment is energy-saving and environmentally friendly. In order to improve the upconversion luminescence efficiency in the far-infrared light region, introducing sensitizer ions is an effective method. The sensitizer transfers the absorbed pump energy to the activator ion through an energy transfer mechanism to enhance luminescence. The sensitizer must effectively absorb the pump energy and effectively transfer it to the activator ion. Yb 3+ The ion is considered to be Er 3+ 、Ho 3+ 、Tm 3+, Tb 3+ , and Pr 3+ ions. The concentration of doped rare earth ions also directly affects the probability of energy transfer. If the concentration is too low, the distance between ions is too large, which hinders the transfer of energy, while too high a concentration may lead to reverse energy transfer and reduce the luminescence efficiency. Therefore, optimizing the doping concentration is crucial. The energy level structure of the luminescence center also plays an important role in the upconversion efficiency. The larger energy gap between higher energy levels and adjacent energy levels reduces the probability of non-radiative transitions, increases the possibility of radiative transitions, and improves the upconversion efficiency. Commonly used pump sources include GaAlAs, AlGaIn, and InGaAs LDs, with emission wavelengths of 979-810nm, 670-690nm, and 940-990nm, respectively. These wavelengths are similar to those of rare earth ions such as Nd 3+ 、Tm 3+ , Er 3+ , and Ho 3+ This explains their widespread use as activators in research.

[0004] Upconversion fluorescence refers to the process in which rare earth ions doped in the lattice convert two or more long-wavelength photons into a single short-wavelength photon. It can be widely used in biomedical imaging, display, lighting, temperature sensing and other fields. However, low upconversion efficiency has become the main bottleneck restricting the practical application of rare earth ion doped upconversion materials. For example, low fluorescence intensity restricts the range of temperature detection, the signal-to-noise ratio of biological imaging, and the output power of lasers. 3+ ) is currently the most common method to enhance the upconversion fluorescence efficiency. This is because Yb 3+ The ions have a large absorption cross-section in the 980nm near-infrared band and can effectively transfer the absorbed energy to most trivalent rare earth ions, such as erbium ions (Er 3+ ), thulium ion (Tm 3+ ) and holmium ions (Ho 3+ ) etc. At present, in order to realize the practical application of rare earth ion doped upconversion materials, further improving the light conversion efficiency of rare earth ion doped upconversion materials is an urgent problem to be solved. As we all know, only when rare earth ions are doped into the lattice can they produce upconversion fluorescence under the action of the surrounding crystal field. Therefore, using metal ions to change the crystal field around rare earth ions to increase the upconversion luminescence intensity will be one of the effective ways. Metal Li +Due to their small radius, ions can easily enter the matrix lattice by substitution or interstitial filling, and the crystal environment around the rare earth ions can be changed by tailoring the lattice field (changing the symmetry of the lattice field), thereby enhancing the upconversion luminescence intensity of the rare earth ions. By optimizing device design and combining new dressings, the application potential of phototherapy in antibacterial and healing is expected to be further expanded. Summary of the invention

[0005] Based on this, the present invention designs a phototherapy dressing with excellent comprehensive mechanical properties, viscosity and antibacterial properties, which will be an important direction for future phototherapy applications. This type of dressing can improve the targeting of phototherapy, reduce the number of treatments, enhance deep antibacterial and healing effects, and further promote its clinical application.

[0006] In order to achieve the above-mentioned invention object, the specific technical scheme is as follows:

[0007] The present invention provides a double ion Yb 3+ -Li + Doped rare earth Pr 3+ : The preparation of the hydrogel dressing of Y2SiO5 upconversion material (CBC-PDA) comprises the following steps:

[0008] (1) Add the purified bacterial cellulose membrane, NHS (N-hydroxysuccinimide) and EDC (1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride) into PBS phosphate buffer solution (pH = 6.0), react overnight (12 h), adjust the pH to alkaline (pH = 8), filter and collect dopamine carboxylated BC (m-BC).

[0009] Further, in step (1), the molar ratio of NHS to EDC is 1 to 1.1:1; the relative amount of the purified bacterial cellulose membrane area and NHS is 6 cm 2 :0.009mol.

[0010] (2) Sodium hyaluronate and sodium periodate are dissolved in a phosphate buffer solution (pH = 5.0), stirred at room temperature in the dark for 4 to 6 hours, and ethylene glycol is added to the reaction solution after stirring to neutralize it. After stirring, the reaction mixture is dialyzed on ultrapure water and freeze-dried to obtain aldehyde-modified sodium hyaluronate.

[0011] Furthermore, in step (2), the molar ratio of sodium hyaluronate to sodium periodate is 1 to 1.1: 1. The molecular weight of the dialysis bag is 1000-15000.

[0012] (3) Aldehyde-modified sodium hyaluronate is dissolved in phosphate buffered saline (pH=5.0), and then dopamine hydrochloride is added and stirred for a period of time. The reaction solution is dialyzed on ultrapure water and freeze-dried to obtain dopamine (PDA)-conjugated AHA (DAHA).

[0013] Furthermore, in step (3), the mass ratio of aldehyde-modified sodium hyaluronate to dopamine hydrochloride is 1:1; and the stirring reaction refers to stirring at 25° C. for 9 to 11 hours.

[0014] (4) DAHA is dissolved in deionized water to obtain a DAHA solution, dopamine carboxylated BC (m-BC) is added, and a solution containing sodium periodate and sodium hydroxide is added, and a hydrogel is quickly formed after mixing, and a CBC-PDA hydrogel is prepared after washing.

[0015] Furthermore, the mass concentration of the DAHA solution is 5%, the pH value of the sodium hydroxide solution is 8.5; and the volume ratio of the DAHA solution to the sodium hydroxide solution is 100:1.

[0016] (5) Yttrium oxide and ytterbium oxide are added to a dilute nitric acid solution to prepare yttrium nitrate and ytterbium nitrate solutions, praseodymium nitrate solution and lithium nitrate solution are added, mixed and heated in a water bath to dissolve, and after dissolution, water is removed by heating until the solution becomes viscous, heating is stopped, a large amount of crystals appear after cooling, and dried to obtain a dry product; the dry product is added to deionized water and anhydrous ethanol to dissolve, TEOS is added, stirred evenly, and heated to mix to form a gel, the gel is dried, crushed, and calcined to obtain a doped dual ion Yb 3+ -Li + @Pr 3+ :Y2SiO5 upconversion material.

[0017] Furthermore, the mass concentration of the diluted nitric acid solution is 32-34%, the mass concentration of the praseodymium nitrate solution is 4-6%, and the mass concentration of the lithium nitrate solution is 20%.

[0018] Further, Yb 3+ -Li + @Pr 3+ :Y2SiO5 precursors include ytterbium oxide (Yb2O3), lithium nitrate (LiNO3), praseodymium nitrate (Pr(NO3)3), yttrium oxide (Y2O3), TEOS (C8H 20 The molar ratio of Yb, Li and Pr is 2:200:100, wherein the molar ratio of Pr to Y2SiO5 satisfies the value of 4-6%, and the optimal loading ratio of Yb is 0.1-0.2% molar ratio relative to Y2SiO5.

[0019] Furthermore, deionized water, anhydrous ethanol and TEOS are prepared in a volume ratio of 4-16:3:1.

[0020] Further, the muffle furnace was calcined to 900-1100°C, the heating rate was 10°C / min, and the temperature was kept for 3 hours after reaching the set temperature. 3+ -Li + @Pr 3+ :Y2SiO5 and hydrogel matrix are mixed to prepare ionic Yb 3+ -Li + Doped rare earth Pr 3+ : Hydrogel dressing of Y2SiO5 upconversion material.

[0021] Furthermore, the upconversion material Yb 3+ -Li + @Pr 3+ :The dosage of Y2SiO5 in hydrogel dressing is: 0.1g / cm 2 .

[0022] The present invention also provides a double ion Yb 3+ -Li + Doped rare earth Pr 3+ : Hydrogel dressing of Y2SiO5 upconversion material (CBC-PDA), hydrogel dressing can be used for wound healing and auxiliary treatment of skin diseases.

[0023] The above one or more technical solutions of the present invention have the following technical effects.

[0024] In order to further improve the upconversion fluorescence intensity, it is planned to introduce metal Li + ions (lithium ions) and Yb 3+ (ytterbium ions) to optimize the lattice field around the rare earth ions:

[0025] ①Introduction of metal ions: Using Li + The smaller radius of the ion is introduced into the matrix lattice by substitution or interstitial filling. When the rare earth ion is doped into the lattice, up-conversion fluorescence can only be generated under the action of the surrounding crystal field. Therefore, using metal ions to change the crystal field around the rare earth ion to increase the up-conversion luminescence intensity will be one of the effective ways. Due to its small radius, the metal Li+ ion is easy to enter the matrix lattice by substitution or interstitial filling, and the crystal environment around the rare earth ion is changed by cutting the lattice field (changing the symmetry of the lattice field), thereby enhancing the up-conversion luminescence intensity of the rare earth ion.

[0026] ② Lattice field control: by adjusting Li + The doping concentration of ions changes the symmetry and local environment of the crystal field, thereby enhancing the upconversion luminescence ability of rare earth ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below.

[0028] Figure 1 Schematic diagram of the preparation principle of (CBC-PDA) hydrogel.

[0029] Figure 2 Schematic diagram of the preparation of upconversion materials.

[0030] Figure 3 Characterization of hydrogel adhesion.

[0031] Figure 4 This is the SEM image of the hydrogel.

[0032] Figure 5 Yb is an up-conversion material 3+ -Li + @Pr 3+ :Y2SiO5XPS.

[0033] Figure 6 0.1% Yb at different calcination temperatures of 900℃, 1000℃, and 1100℃ 3+ -Li + @Pr 3+ Fluorescence spectra of upconversion materials.

[0034] Figure 7 0.2% Yb at different calcination temperatures of 900℃, 1000℃, and 1100℃ 3+ -Li + @Pr 3+ : Fluorescence spectrum of Y2SiO5 upconversion material.

[0035] Figure 8 Li at different calcination temperatures of 900℃, 1000℃, and 1100℃ + @Pr 3+ : Fluorescence spectrum of Y2SiO5 upconversion material.

[0036] Fig. 9 Pr is calcined at 900℃ 3+ :Different praseodymium ion doping amounts (0, 0.5%, 1%, 5%, 8% Pr 3+ )’s fluorescence spectrum.

[0037] Fig.10 Pr prepared with different TEOS:H2O volume ratios 3+ : Emission spectrum of Y2SiO5.

[0038] Fig.11 Yb prepared in Example 7 3+ @Pr3+ :Different Yb in Y2SiO5 upconversion materials 3+ Emission spectra of molar concentration doping amount. DETAILED DESCRIPTION

[0039] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0040] Throughout the specification, unless otherwise specified, the terms used herein should be understood as commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification shall prevail. Figure 1 As shown, the (CBC-BC) hydrogels prepared in Examples 1-3 were all prepared by this process.

[0041] Example 1

[0042] A double ion Yb 3+ -Li + Doped rare earth Pr 3+ : A method for preparing a hydrogel of a Y2SiO5 upconversion material (CBC-PDA), comprising the following steps:

[0043] S1, bacterial cellulose (BC) purification—CBC.

[0044] Take a 500mL beaker, use an electronic balance to weigh 2g of NaOH on weighing paper and place it in the 500mL beaker, take 500mL of distilled water and pour it into the beaker to prepare a 0.1mol / L NaOH solution. Cut the BC membrane (6cm 2 ), immersed in the NaOH solution prepared in step (1). Place the beaker in a constant temperature (90℃~95℃) oil bath and heat for 2 hours to complete the purification of BC. After 2 hours, take out and cool to room temperature, take out the BC membrane, rinse the BC membrane with distilled water several times until the pH is neutral, freeze in the refrigerator and use freeze drying for 24 hours to obtain the purified BC membrane.

[0045] S2, dopamine carboxylated BC-(CBC-PDA). Pure BC membrane was added with 0.009 mol NHS (N-hydroxysuccinimide) and 0.0085 mol EDC (1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride) and weighed, and then put into phosphate buffered saline (PBS, pH=5.0) to fully dissolve and react for 12 hours before adjusting the solution to pH=8.

[0046] S3, Synthesis of dopamine (PDA) conjugated AHA (DAHA).

[0047] (1) 0.0025 mol sodium hyaluronate (C 14 H 22 NNaO 11 ) and 0.0023 mol sodium periodate (NaIO4) were dissolved in 100 mL phosphate buffered saline (PBS, pH = 5.0) and stirred at room temperature in the dark for 5 hours.

[0048] (2) 1 mL of ethylene glycol (C2H6O2) was added to the reaction solution to neutralize the excess sodium periodate (NaIO4). The mixture was dialyzed in ultrapure water for 48 hours and freeze-dried to obtain AHA (aldehyde-modified sodium hyaluronate).

[0049] (3) Dissolve 1.0 g of AHA in 100 mL of phosphate buffered saline (PBS, pH = 5.0), then add 1.0 g of dopamine hydrochloride and stir at 25°C for 10 h.

[0050] (4) The reaction solution was dialyzed in ultrapure water for 48 hours and lyophilized to obtain DAHA.

[0051] S4, Preparation of CBC-PDA hydrogel:

[0052] 5 g DAHA was dissolved in 100 g deionized water to obtain a DAHA solution, dopamine carboxylated BC (m-BC) was added, and 3.865 g sodium periodate and 1 mL sodium hydroxide solution (adjusted to pH = 8.5) were added. After mixing, a hydrogel was quickly formed, and the solution was rinsed three times with deionized water to remove residual sodium periodate to prepare a CBC-PDA hydrogel.

[0053] S5: Yb 3+ -Li + @Pr 3+ :Preparation of Y2SiO5 upconversion material:

[0054] (1) Take 1×10 -41. 0.02 g powder mass, Yb2O3, 0.01 mol lithium nitrate (20% solution, 3.45 g solution mass, LiNO3), 0.1 mol yttrium oxide (22.58 g powder mass, Y2O3) are added to a diluted nitric acid solution (concentration after dilution is 32-34%) in a beaker to prepare a mixed solution of yttrium nitrate and ytterbium nitrate, 0.005 mol praseodymium nitrate (Pr(NO3)3 mass fraction is 4.36% solution, 39 g solution mass), 0.1 mol yttrium oxide (22.58 g powder mass, Y2O3), mixed and heated in a water bath at 80°C to dissolve, heated in an electric furnace after dissolution to remove moisture until the solution becomes viscous, stopped heating, cooled to obtain a large amount of crystals, dried in an oven at 104°C to obtain a dry product;

[0055] (2) The dried product was dissolved in deionized water and anhydrous ethanol, and 20.8 g TEOS (0.1 mol) was added. The deionized water, anhydrous ethanol, and TEOS were prepared in a volume ratio of 16:3:1. After stirring evenly, the mixture was heated at 70°C to form a gel. The gel was dried at 104°C. The sample was crushed in a mortar and calcined in a muffle furnace. The calcination method was programmed heating at a heating rate of 10°C / min. The temperature was raised to 1000°C and calcined for 3 hours to obtain doped dual ion Yb 3+ -Li + @Pr 3+ : Y2SiO5 upconversion material. The molar doping amount of Pr in Y2SiO5 is 5%; and the optimal loading ratio of Yb is 0.2% molar ratio relative to Y2SiO5. Therefore, the lithium ion Li + The doping molar percentage is used as a preamble, and the sample name is recorded as 1100℃ 0.2% Yb 3+ -Li + @5%Pr 3+ :Y2SiO5.

[0056] S6: doped with double ion Yb 3+ -Li + @Pr 3+ :Y2SiO5 upconversion material (CBC-PDA) hydrogel dressing: according to 0.1g / cm 2 The amount of up-conversion material added, adding Yb 3+ -Li + @Pr 3+ : Y2SiO5 and hydrogel (CBC-PDA) are stirred and mixed.

[0057] The embodiments were subjected to relevant chemical tests, and the test conditions all adopted relevant national standards.

[0058] like Figure 1 As shown, doping with double ion Yb3+ -Li + @Pr 3+ :Schematic diagram of the preparation of hydrogel dressing based on Y2SiO5 upconversion material (CBC-PDA).

[0059] like Figure 2 As shown, doping with double ion Yb 3+ -Li + @Pr 3+ :Schematic diagram of the preparation of hydrogel dressing of Y2SiO5 upconversion material (CBC-PDA).

[0060] like Figure 3 As shown, (CBC-PDA) hydrogel has good adhesion and can adhere to the mouse organs heart, liver, spleen, lung, and kidney. It can also adhere to laboratory A4 paper, beakers, tweezers, and small glass bottles.

[0061] like Figure 4 As shown, the interior of the (CBC-PDA) hydrogel is a porous network structure. The presence of large pores can absorb wound fluid and allow gas exchange to prevent wound ulceration.

[0062] like Figure 5 As shown, the full scan spectrum shows that the sample 1000℃ 0.2% Yb 3+ -Li + @Pr 3+ :Y2SiO5 contains Si, O, C, Y, Li, Yb, and Pr elements. The peak at around 54.5eV is Li1s. The peak at around 284.5eV is CC bond, the peak at around 286eV is CO bond, and the peak at around 288.5eV is C=O bond. The peak at around 102eV is Si-O2p. The peak at around 160eV is Y3d3 / 2. The peak at around 157.5eV is Y3d5 / 2. The peak at around 153.5eV is Si2s. The peak at around 954eV is Pr3d3 / 2. And the peak at around 935eV is Pr3d5 / 2. The peak at around 185eV is Yb 3+ 4d, indicating that Yb exists in trivalent form.

[0063] Example 2

[0064] Based on the doping double ion 0.2% Yb in Example 1 3+ -Li + @Pr 3+ :Y2SiO5 upconversion material, study the effect of calcination temperature in step S5 on doping with dual ion Yb 3+ -Li + @Pr 3+:The influence of Y2SiO5 on the upconversion fluorescence intensity. 3+ -Li + @Pr 3+ : Y2SiO5 upconversion material. 1100℃ 0.2% Yb 3+ -Li + @Pr 3+ :Y2SiO5、1000℃0.2%Yb 3+ -Li + @Pr 3+ :Y2SiO5、900℃0.2%Yb 3+ -Li + @Pr 3+ .

[0065] According to the up-conversion fluorescence spectrum Figure 7 It is known that in the infrared region of 200-700nm, 1100℃ 0.2% Yb 3+ -Li + @Pr 3+ :Y2SiO5 fluorescence intensity at 240nm is 2.12×10 4 cps; 1000℃0.2%Yb 3+ -Li + @Pr 3+ :Y2SiO5 fluorescence intensity at 240nm is 1.06×10 5 cps; 900℃0.2%Yb 3+ -Li + @Pr 3+ The fluorescence intensity at 240 nm was 6.37×10 4 cps.

[0066] Example 3

[0067] Based on the doping double ion 0.2% Yb in Example 1 3+ -Li + @Pr 3+ :Y2SiO5 upconversion material, changing Yb 3+ The molar concentration of doping is 0.1%. The effect of calcination temperature in step S5 on the doping of dual ions 0.1% Yb 3+ -Li + @Pr 3+ :The influence of Y2SiO5 on the upconversion fluorescence intensity. 3+ -Li + @Pr 3+ : Y2SiO5 upconversion material. 1100℃ 0.1% Yb3+ -Li + @Pr 3+ :Y2SiO5、1000℃0.1%Yb 3+ -Li + @Pr 3+ :Y2SiO5、900℃0.1%Yb 3+ -Li + @Pr 3+ .

[0068] According to the up-conversion fluorescence spectrum Figure 6 It is known that in the infrared region of 200-700nm, 900℃ 0.1% Yb 3+ -Li + @Pr 3+ :Y2SiO5 fluorescence intensity at 240nm is 805000cps; 1000℃ 0.1% Yb 3+ -Li + @Pr 3+ :Y2SiO5 fluorescence intensity at 2400nm is 537000cps; 1100℃0.1%Yb 3+ -Li + @Pr 3+ The fluorescence intensity at 240nm is 940000cps.

[0069] Example 4

[0070] 1000℃Li + @Pr 3+ : The preparation of Y2SiO5 is different from that of Example 1 except that no Yb 3+ , Li + @Pr 3+ : Y2SiO5 upconversion material. At different calcination temperatures, 1100℃Li + @Pr 3+ :Y2SiO5、1000℃Li + @Pr 3+ :Y2SiO5、900℃Li + @Pr 3+ :Y2SiO5. According to the up-conversion fluorescence spectrum Figure 8 It is known that in the infrared region of 200-700nm, 1100℃Li + @Pr 3+ :Y2SiO5 fluorescence intensity at 240nm is 1.06×10 5 cps; 1000℃Li + @Pr 3+ :Y2SiO5 fluorescence intensity at 240nm is 7.43×104 cps; 900℃

[0071] Li + @Pr 3++ :Y2SiO5 fluorescence intensity at 240nm is 7.43×10 4 cps.

[0072] Example 5

[0073] Without the doping of Yb and Li, Pr 3+ : Y2SiO5 was calcined at 900°C to study the effect of Pr doping on fluorescence intensity. Other operations were the same as those of Example 1. 3+ :Y2SiO5 preparation conditions are the same. The praseodymium ion doping amount in the "nitric acid spectrum solution" of Example 1 was changed to 0.5%, 1%, 5%, and 8% respectively. 900℃ 0.5% Pr 3+ :Y2SiO5、900℃1%Pr 3+ :Y2SiO5、900℃5%Pr 3+ :Y2SiO5、900℃8%Pr 3+ :Y2SiO5.

[0074] Table 1: Pr 3+ Concentration (900℃)

[0075] Doping amount <![CDATA[Pr(NO3)3]]> TEOS (6) Add water when dissolving Ethanol Group 1 0.5% 29μL 0.60g 9.6mL 28.8mL Group 2 1% 586μL 0.60g 9.6mL 28.8mL Group 3 5% 3100μL 0.62g 9.92mL 29.76mL Group 4 8% 5000μL 0.66g 10.6mL 31.8mL

[0076] Fig. 9 It shows that when the concentration of praseodymium is 0.5%-1%, the fluorescence intensity is low; when the doping concentration of praseodymium is 5%, its fluorescence intensity increases significantly; and when the doping amount of praseodymium element continues to increase to 8%, its fluorescence intensity weakens instead, because the high doping concentration will cause fluorescence concentration quenching. Therefore, with the increase of the doping amount of praseodymium element, the fluorescence intensity first increases and then decreases. When the doping amount of praseodymium is 5%, the up-conversion phosphor has a good up-conversion fluorescence effect, and the fluorescence intensity is 80000cps.

[0077] Embodiment 6:

[0078] Without involving Yb and Li doping, the volume ratio of tetraethyl orthosilicate (TEOS) and deionized water (H2O) of 1:16, 1:13, and 1:4 was studied for the effect of Pr 3+ :Y2SiO5 fluorescence intensity. Other operations are the same as those of Example 1. 3+ : The preparation conditions of Y2SiO5 are the same.

[0079] Table 2: Yttrium-praseodymium silicate optimization - TEOS:H2O (water content)

[0080]

[0081] TEOS is a Si connected to four -OCH2CH3. When TEOS is hydrolyzed, the -OCH2CH3 connected to Si is disconnected, so the volume ratio of TEOS:H2O is 1:4. In the hydrolysis process of ethyl silicate, in order to fully hydrolyze ethyl silicate, the water content should be appropriately increased. However, too much water content will lead to too low a solution concentration and too slow a hydrolysis rate. Therefore, the samples prepared with a TEOS:H2O volume ratio of 1:13, 1:16 and a TEOS:H2O molar ratio of 1:4 were selected for comparison. According to the upconversion fluorescence spectrum Fig.10 It is known that the emission intensity at 310nm when TEOS:H2O is 1:16 is 8715.7cps, which is greater than the emission intensity of 8595.795 when TEOS:H2O is 1:13 and the emission intensity of 8395.795 when TEOS:H2O is 1:4.

[0082] Embodiment 7:

[0083] 1000℃Yb 3+ @Pr 3+ : The preparation of Y2SiO5 is different from that of Example 1 except that Li + , Yb 3 + @Pr 3+ : Y2SiO5 upconversion material. 0.05% Yb 3+ @Pr 3+ :Y2SiO5、0.1%Yb 3+ @Pr 3+ :Y2SiO5、0.15%Yb 3+ @Pr 3+ 、0.2%Yb 3+ @Pr 3+ 、0.25%Yb 3+ @Pr 3+ According to the upconversion fluorescence spectrum Fig.11 It is known that in the infrared region of 400-700nm, 1000℃ 0.05% Yb 3+ @Pr 3+ :Y2SiO5 fluorescence intensity at 475nm is 1960cps; 1000℃0.1%Yb 3+ @Pr 3+ :Y2SiO5 fluorescence intensity at 475nm is 7100cps; 1000℃ 0.15% Yb 3+ @Pr 3+ The fluorescence intensity at 475nm is 1299cps; 1000℃0.2%Yb 3+ @Pr 3+Fluorescence intensity at 475nm is 3011cps; 1000℃0.25%Yb 3+ @Pr 3+ The fluorescence intensity at 475 nm was 514 cps.

[0084] In summary, the hydrogel provided by the present invention relies on hyaluronic acid as a natural component of the extracellular matrix, and has good biocompatibility, biodegradability and gelation. In addition, it can also mediate cell signal transduction, promote cell migration and proliferation, and thus promote tissue regeneration. For these reasons, hyaluronic acid is considered to be a very attractive tissue adhesive. The adhesion properties of hyaluronic acid can be improved by grafting dopamine onto the hyaluronic acid chain, which is a basic requirement for hyaluronic acid when used in the surgical field. The catechol group can make the hyaluronic acid tissue adhesive have good antioxidant capacity, which is conducive to wound tissue healing. Bacterial cellulose (BC): Bacterial cellulose is an ultrapure cellulose produced by bacterial metabolism, which is biocompatible and biodegradable. Its nanoscale three-dimensional network structure gives it excellent mechanical properties. The production process is environmentally friendly and does not require a high-energy purification step. Polydopamine (PDA): The molecular structure of PDA is similar to that of mussel adhesion proteins, and it has a unique role in the cell affinity and adhesion of materials. Through interaction with various surfaces, PDA can improve the adhesion properties of materials. PDA can also be used to prepare cell-friendly antibacterial hydrogels, combined with silver nanoparticles to provide antibacterial effects. Nanocrystal technology: Increase the effectiveness of drugs in skin applications by improving their saturation and solubility. In order to prolong the retention time of nanocrystals in the skin, hydrogels can be used as their effective carriers. Near-infrared phototherapy: Near-infrared phototherapy includes photodynamic therapy and photothermal therapy, which can kill bacteria through reactive oxygen or use high temperature to sterilize, and is not easy to produce bacterial resistance. Upconversion nanomaterials (UCNPs) have excellent photodynamic and photothermal properties under near-infrared light and are a new type of antibacterial material.

Claims

1. A double ion Yb 3+ -Li + Doped rare earth Pr 3+ : A method for preparing a Y2SiO5 upconversion material hydrogel dressing, characterized in that: In the double ion Yb 3+ -Li + Doped rare earth Pr 3+ :Y2SiO5 upconversion material is mixed with hydrogel material to prepare dual ion Yb 3+ -Li + Doped rare earth Pr 3+ : Y2SiO5 upconversion material hydrogel dressing; wherein the amount of Pr is equivalent to 4-6% of the molar amount of Y2SiO5; the amount of Yb is relative to 0.1-0.3% of the molar amount of Y2SiO5.

2. According to claim 1, the double ion Yb 3+ -Li + Doped rare earth Pr 3+ : A method for preparing a Y2SiO5 upconversion material hydrogel dressing, characterized in that: Double ion Yb 3+ -Li + Doped rare earth Pr 3+ :The preparation method of Y2SiO5 upconversion material is: (1) adding yttrium oxide and ytterbium oxide to nitric acid to obtain yttrium nitrate and ytterbium nitrate solutions, mixing them with praseodymium nitrate and lithium nitrate, heating in a water bath to remove water until the solution becomes viscous, stopping heating and cooling naturally to gradually crystallize, and drying to obtain a dried product; (2) Add the dried product to a mixed solution of deionized water and anhydrous ethanol, add TEOS after it is fully dissolved, stir evenly, and heat and mix to form a gel. The gel is dried, crushed, and calcined to obtain doped dual-ion Yb 3+ -Li + @Pr 3+ : Y2SiO5 upconversion powder material.

3. According to claim 2, the double ion Yb 3+ -Li + Doped rare earth Pr 3+ : A method for preparing a Y2SiO5 upconversion material hydrogel dressing, characterized in that: The molar dosage relationship among the raw materials of ytterbium oxide, lithium nitrate, praseodymium nitrate, yttrium oxide and TEOS is 1-4:200:100:2000:2000.

4. According to claim 2, the double ion Yb 3+ -Li + Doped rare earth Pr 3+ : A method for preparing a Y2SiO5 upconversion material hydrogel dressing, characterized in that: The volume ratio of ionized water, anhydrous ethanol and TEOS is 4-16:3:

1.

5. According to claim 3, the double ion Yb 3+ -Li + Doped rare earth Pr 3+ : A method for preparing a Y2SiO5 upconversion material hydrogel dressing, characterized in that: The molar ratio of Yb, Li and Pr is 2:200:

100.

6. According to claim 2, the double ion Yb 3+ -Li + Doped rare earth Pr 3+ : A method for preparing a Y2SiO5 upconversion material hydrogel dressing, characterized in that: The calcination temperature is 900-1100° C., the heating rate is 10° C. / min, and the calcination time is 2-4 hours.

7. According to claim 1, the double ion Yb 3+ -Li + Doped rare earth Pr 3+ : A method for preparing a Y2SiO5 upconversion material hydrogel dressing, characterized in that: The preparation method of the hydrogel material is as follows: (1) adding the purified bacterial cellulose, N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide to a PBS phosphate buffered saline solution for reaction for 12 hours, adjusting the pH to alkaline, filtering, and collecting dopamine carboxylated bacterial cellulose; (2) dissolving sodium hyaluronate and sodium periodate in a phosphate buffered saline solution, stirring for a period of time at room temperature in the dark, adding ethylene glycol to the reaction solution after stirring to neutralize it, dialyzing the reaction mixture on ultrapure water, and freeze-drying to obtain aldehyde-modified sodium hyaluronate; dissolving aldehyde-modified sodium hyaluronate in a phosphate buffered saline solution, then adding dopamine hydrochloride, stirring for a period of time, dialyzing the reaction solution on ultrapure water, and freeze-drying to obtain hyaluronic acid-dopamine, which is calculated as DAHA; (3) DAHA is dissolved in deionized water, dopamine carboxylated bacterial cellulose is added, and the mixture is mixed with a solution containing sodium periodate and sodium hydroxide to rapidly form a hydrogel, and the CBC-PDA hydrogel is prepared after washing.

8. According to claim 7, the double ion Yb 3+ -Li + Doped rare earth Pr 3+ : A method for preparing a Y2SiO5 upconversion material hydrogel dressing, characterized in that: The upconversion powder material Yb 3+ -Li + @Pr 3+ :Y2SiO5 was mixed with CBC-PDA hydrogel matrix to prepare Yb 3+ -Li + Doped rare earth Pr 3+ : Y2SiO5 upconversion hydrogel dressing.

9. The diionic Yb prepared according to any one of claims 1 to 8 3+ -Li + Doped rare earth Pr 3+ : Y2SiO5 upconversion material hydrogel dressing.

10. The double ion Yb according to claim 9 3+ -Li + Doped rare earth Pr 3+ :Application of Y2SiO5 upconversion material hydrogel dressing in wound healing and auxiliary treatment of skin diseases.